The impact of implementing the Odoo cloud- based enterprise resource planning systeme on the accountant profession: A case study of the Hasnaoui Company Complex in the wilaya of Sidi Bel Abbes. - elbahi, mohamed amine; slimani, malika (Journal of Research in Finance and Accounting, 2024)
In the context of the fourth industrial revolution, the application of information technology to improve business processes and provide advice and services has become more commonplace, Cloud-based Enterprise Resource Planning (CERP) systems are being used by businesses as an effective solution to reduce costs, reduce workload, save time and manage resources efficiently. The study aimed to present cloud-based enterprise resource planning systems and how they affect the role, status and responsibility of accountants, who have had to acquire new skills to adapt to the working conditions that characterise these systems, Highlighting the impact of the Odoo cloud-based enterprise resource planning system on the accounting profession through a case study of the Hasnaoui group of companies in the wilaya of Sidi Bel Abbès, A quiz was used as a data collection tool, where a sample size of (61 employees) in the accounting field was analysed using the SPSS program,The study concluded with a number of results, the most important of which are : There is no statistically significant relationship between the Odoo cloud-based enterprise resource planning system and the accounting profession in the Hasnaoui group of companies in the wilaya of Sidi Bel Abbès.